Hubungan Tingkat Loneliness dengan Parasocial Relationship pada Mahasiswa Penggemar K-Pop - Hartika Utami Fitri; Manah Rasmanah; Tuzzahra, Shona (DA'WA: Jurnal Sosial dan Dakwah, 2025)
Students are vulnerable to experiencing loneliness. Students with high psychosocial pressure such as loneliness and depression tend to be more comfortable interacting socially online than social activities in person, and one of them is making parasocial relationships an alternative. This study looked at whether there was a relationship between the level of loneliness and parasocial relationships in K-Pop fan students. The sample of this study was 159 respondents and the sampling technique was purposive. Data was collected by questionnaire. In measuring loneliness variables, they adapted a questionnaire from the research of J.D.J. Gierveld and Van Tilburg. Meanwhile, parasocial relationships are measured by the Celebrity Attitude Scale (CAS) created by Maltby. The results of the study showed that students who were interested in K-pop had a moderate level of loneliness (80%) and a moderate level of parasocial relationship (73%). Using a simple linear regression with a significance level of 5%, the study found that the R Square value was 0.243, which means that there was a relationship between loneliness and parasocial relationships in k-pop fan students, which was 24.3% so that the alternative hypothesis (Ha) and the null hypothesis (H0) were rejected.